2023
DOI: 10.3390/ijms24087441
|View full text |Cite
|
Sign up to set email alerts
|

OsJRL40, a Jacalin-Related Lectin Gene, Promotes Salt Stress Tolerance in Rice

Abstract: High salinity is a major stress factor affecting the quality and productivity of rice (Oryza sativa L.). Although numerous salt tolerance-related genes have been identified in rice, their molecular mechanisms remain unknown. Here, we report that OsJRL40, a jacalin-related lectin gene, confers remarkable salt tolerance in rice. The loss of function of OsJRL40 increased sensitivity to salt stress in rice, whereas its overexpression enhanced salt tolerance at the seedling stage and during reproductive growth. β-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Most functionally known JRLs in subgroup 1 are involved in agglutinating activity [35,50,52,56], which demonstrated that proteins from the same subgroup may display similar roles. Meanwhile, two members in subgroup 7, Orysata and HvHorcH, both confer a tolerance to salt stress [31,51], and the member OsJRL40 in subgroup 10 also positively regulated salt stress tolerance [30]. Both OsJAC1 and TaJA1 in subgroup 1 were associated with pathogen resistance [21,49,50], and TaJRLL1 in subgroup 6 was also involved in pathogen resistance [16].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Most functionally known JRLs in subgroup 1 are involved in agglutinating activity [35,50,52,56], which demonstrated that proteins from the same subgroup may display similar roles. Meanwhile, two members in subgroup 7, Orysata and HvHorcH, both confer a tolerance to salt stress [31,51], and the member OsJRL40 in subgroup 10 also positively regulated salt stress tolerance [30]. Both OsJAC1 and TaJA1 in subgroup 1 were associated with pathogen resistance [21,49,50], and TaJRLL1 in subgroup 6 was also involved in pathogen resistance [16].…”
Section: Discussionmentioning
confidence: 98%
“…JRL are widely distributed in plants and are found in many species, including Arabidopsis, rice, wheat, maize, barley, Sorghum bicolor, and Musa acuminata [2]. Several of them have been demonstrated to be involved in plant growth regulation and stress responses [3,10,28,30,31,54]. Owing to their essential roles, the identification and characterization of JRL gene families and their expression profiles in response to abiotic stresses have been performed at the genome-wide level in several plant species, such as rice, wheat, and moso bamboo [2,3,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increases antioxidant enzymatic activities and maintains the balance of Na + /K + during salinity stress. Manages rice's salt stress by regulating the expression of genes responsible for transporting Na + /K + , as well as genes involved in salt-responsive transcription factors and proteins [322] OsSAPK4…”
Section: Oscpk12mentioning
confidence: 99%